Prevalencia del metastrongylus en el tracto respiratorio en cerdos en el camal de salcedo. - Onofre Viteri, Erika Alejandra (2021)
Metastrongylus or verminous bronchopneumonia is a parasitic airway disease that affects especially young pigs that have not reached 6 months of age. These are infected by the consumption of earthworms. This is one of the most important parasitosis that affects pigs, causing severe damage such as strong coughing, lack of appetite, diarrhea and even the death of animals, thus leaving irreversible damage for small and large pig producers which affect their economy. In this research study the postmortem diagnosis of pulmonary parasites was carried out in pigs that were slaughtered in the municipal slaughterhose in Salcedo Canton. The aim was the characterization of the prevalence of Metastrongylus spp. in the respiratory tract in pigs, determined by the methods of bronchoalveolar lavage and scraping. An epidemiological map was made to sectorize the high or low prevalence of parasites associated with Metastrongylus and propose a preventive and recovery action plan according to the epizootiological situation of Metastrongylus to prevent its spread and become zoonotic. The samples were taken from 200 pigs that entered the slaughterhouse, two diagnostic techniques were used: bronchoalveolar lavage and scraping being identified by numbering. The genus of parasites that was found is metatrongylus apri with 1%, which is one of the most common. It was concluded that in the Municipal slaughterhouse in Salcedo Canton, the prevalence of Metastrongylus spp, is very low since the farms and pig owners maintain a very regular de-worming system for their animals. As a result at the moment of slaughter they were healthy with a good physical build, with a level of lean meat, in order to ensure that it does not cause zoonoses for consumers, through the methods of scraping and bronchoalveolar lavage was possible to determined that the most effective technique was bronchoalveolar lavage since a sample of the entire lung was obtained and there was a greater probability of its finding. An epidemiological map of the studied Canton was developed. Therefore, it has a low prevalence of Metastrongylus spp. A preventive action plan was also proposed in which the frequency of de-worming that pigs must have both from birth to slaughter was explained, as well as the biosecurity measures for pig pens.